An epidemiological and genetic study of facial clefting in France. II Segregation analysis. Issue 6 (December 1984) - Demenais, F; Bonaïti-Pellié, C; Briard, M L; Feingold, J
Abstract : Familial transmission of cleft lip with or without cleft palate (CL(P] and isolated cleft palate (CP) was studied in two French samples of 458 CL(P) and 156 CP nuclear families, using the recently implemented unified model. In neither case could discrimination be achieved between polygenic inheritance and monogenic inheritance with a high proportion of sporadic cases. In this type of disorder with a complex genetic basis the information furnished by such an approach, which only considers the affected status, is discussed. Future investigations on the joint familial transmission of the disease and different marker systems may help to identify the genes involved in these developmental anomalies.